SEREAL UMBI SATOIMO (COLOCASIA ESCULENTA VAR. ANTIQUORUM) PRODUK PANGAN ANTI DIABETES MELITUS DALAM MASA ADAPTASI KEBIASAAN BARU - TITA FITRIANA SUKMAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The Covid-19 pandemic has affected all aspects of human life, including the health of groups of people with co-morbidities such as diabetes mellitus. According to data from the Ministry of Health (2020) the most patients who have died have contributed to diabetes mellitus. This requires preventive action and treatment in terms of diet and dietary intake of nutrients for patients. One alternative solution that can be done is to fulfill the intake of carbohydrates to replace rice into easily digestible fiber, which comes from tubers or taro. Satoimo tubers have been widely planted by the community but have not been massively developed into healthy food products for people with diabetes mellitus as an effort to control spikes in blood sugar levels and the transmission of Covid-19. This study developed quality standards for the characteristics of satoimo tuber flour and ready-to-eat cereals with a low glycemic index that are safe for consumption. This research is a qualitative research conducted in the chemistry laboratory of SMA N 1 Kembangbahu Lamongan then tested for ash content and total sugar test at BARISTAND Surabaya. The processing of satoimo tubers into satoimo taro flour goes through several stages, namely, peeling, slicing, soaking, blanching, bleaching, drying, milling, sifting. Test the ash content of satoimo flour at 0.20% so it is suitable for consumption. The use of satoimo tuber flour which is dominant in food ingredients makes the total sugar content of A1 cereal 2.98% lower so it is highly recommended for people with diabetes mellitus as a substitute for carbohydrates that are low in sugar and low on the glycemic index. ABSTRAKMasa pandemi Covid-19 mempengaruhi segala aspek kehidupan manusia, tidak terkecuali kesehatan kelompok mayarakat dengan penyakit penyerta (komorbid) seperti penderita diabetes melitus. Menurut data Kemenkes (2020) pasien terbanyak dan mengalami kematian banyak disumbang oleh penderita diabetes melitus. Hal tersebut perlu tindakan preventif dan perawatan dalam segi pola makan dan asupan diet nutrisi bagi pasien. Salah satu solusi alternatif yang dapat dilakukan adalah dengan pemenuhan asupan karbohidrat pengganti beras menjadi serat yang mudah dicerna yaitu berasal dari umbi atau talas. Umbi satoimo sudah banyak ditanam oleh masyarakat namun belum dikembangkan secara masif menjadi produk pangan sehat untuk penderita diabetes melitus sebagai upaya menjaga lonjakan kadar gula dalam darah serta penularan Covid-19. Penelitian ini mengembangkan baku mutu karakteristik produk tepung umbi satoimo serta sereal siap santap rendah indeks glikemik yang aman dikonsumsi. Penelitian ini adalah penelitian kualitatif yang dilakukan di laboratorium kimia SMA N 1 Kembangbahu Lamongan kemudian uji kadar abu dan uji gula total di BARISTAND Surabaya. Pengolahan umbi satoimo menjadi tepung talas satoimo melalui beberapa tahapan yaitu, pengupasan, pengirisan, perendaman, blanching, bleaching, pengeringan, penggilingan, pengayakan. Uji kadar abu tepung satoimo sebesar 0,20% sehingga layak untuk dikonsumsi. Penggunaan tepung umbi satoimo yang dominan pada bahan makanan menjadikan kadar gula total sereal A1 2,98% lebih rendah sehingga sangat direkomendasikan bagi penderita diabetes melitus sebagai pengganti karbohidrat yang rendah gula dan rendah indeks glikemik.